Macrophage‐Specific Hypoxia‐Inducible Factor‐1α Contributes to Impaired Autophagic Flux in Nonalcoholic Steatohepatitis. Issue 2 (4th January 2019) - Wang, Xiaojing; de Carvalho Ribeiro, Marcelle; Iracheta‐Vellve, Arvin; Lowe, Patrick; Ambade, Aditya; Satishchandran, Abhishek; Bukong, Terence; Catalano, Donna; Kodys, Karen; Szabo, Gyongyi
Abstract : Inflammatory cell activation drives diverse cellular programming during hepatic diseases. Hypoxia‐inducible factors (HIFs) have recently been identified as important regulators of immunity and inflammation. In nonalcoholic steatohepatitis (NASH), HIF‐1α is upregulated in hepatocytes, where it induces steatosis; however, the role of HIF‐1α in macrophages under metabolic stress has not been explored. In this study, we found increased HIF‐1α levels in hepatic macrophages in methionine‐choline‐deficient (MCD) diet‐fed mice and in macrophages of patients with NASH compared with controls. The HIF‐1α increase was concomitant with elevated levels of autophagy markers BNIP3, Beclin‐1, LC3‐II, and p62 in both mouse and human macrophages. LysM Cre HIF dPA fl/fl mice, which have HIF‐1α levels stabilized in macrophages, showed higher steatosis and liver inflammation compared with HIF dPA fl/fl mice on MCD diet. In vitro and ex vivo experiments reveal that saturated fatty acid, palmitic acid (PA), both induces HIF‐1α and impairs autophagic flux in macrophages. Using small interfering RNA–mediated knock‐down and overexpression of HIF‐1α in macrophages, we demonstrated that PA impairs autophagy via HIF‐1α. We found that HIF‐1α mediates NF‐κB activation and MCP‐1 production and that HIF‐1α—mediated impairment of macrophage autophagy increases IL‐1β production, contributing to MCD diet‐induced NASH. Conclusion : Palmitic acid impairs autophagy via HIF‐1α activation in macrophages. HIF‐1α and impaired autophagy are present in NASH in vivo in mouse macrophages and in human blood monocytes. We identified that HIF‐1α activation and decreased autophagic flux stimulate inflammation in macrophages through upregulation of NF‐κB activation. These results suggest that macrophage activation in NASH involves a complex interplay between HIF‐1α and autophagy as these pathways promote proinflammatory overactivation in MCD diet‐induced NASH.